Associations between MTHFR gene polymorphisms and the risk of intracranial hemorrhage: Evidence from a meta‐analysis - Fenghui Wang; Zhendong Xu; Haiyan Jiao; Aixiang Wang; Youbin Jing (Brain and Behavior, 2021)
Abstract Introduction Previously, a number of genetic epidemiological studies have evaluated associations between MTHFR gene polymorphisms and the risk of intracranial hemorrhage (ICH), with controversial results. Accordingly, we carried out this meta‐analysis to more conclusively evaluate associations between MTHFR gene polymorphisms and the risk of ICH. Methods MEDLINE, EMBASE, Wanfang, VIP, and CNKI were searched comprehensively, and thirty‐one genetic association studies were finally selected to be included in this meta‐analysis. Results Eight literatures (963 cases and 2,244 controls) assessed relationship between MTHFR rs1801131 (A1298C) polymorphism and the risk of ICH, and thirty‐one literatures (3,679 cases and 9,067 controls) assessed relationship between MTHFR rs1801133 (C677T) polymorphism and the risk of ICH. We found that AA genotype of rs1801131 polymorphism was significantly associated with a decreased risk of intraventricular hemorrhage (IH) compared with AC/CC genotypes (OR = 0.63; p = .003), AC genotype was significantly associated with an increased risk of IH compared with AA/CC genotypes (OR = 1.55; p = .005), and A allele was significantly associated with a decreased risk of IH compared with C allele (OR = 0.75; p = .02). Additionally, CC genotype of rs1801133 polymorphism was significantly associated with a decreased risk of cerebral hemorrhage (CH) compared with CT/TT genotypes (OR = 0.75; p = .04), TT genotype was significantly associated with an increased risk of CH compared with CC/CT genotypes (OR = 1.27; p = .02), and C allele was significantly associated with a decreased risk of CH compared with T allele (OR = 0.85; p = .007). Conclusions This meta‐analysis shows that rs1801131 polymorphism may influence the risk of IH, while rs1801133 polymorphism may influence the risk of CH.